From oscillatory to non-oscillatory disturbances: A comparative review of root cause analysis methods. (May 2022) - Lucke, Matthieu; Chioua, Moncef; Thornhill, Nina F.
Abstract: This paper reviews existing data-driven methods according to three criteria: the properties of the method, the impact of the systems through which the disturbance propagates on the results of the method, and the types of disturbances covered by the method. The comparative review is used to derive guidelines for Root Cause Analysis (RCA) of oscillatory and non-oscillatory disturbances in industrial processes. In particular, it suggests an approach for RCA of transient disturbances based on methods for detection of transient disturbances. The comparative review is targeting primarily engineers working on Fault Detection and Diagnosis (FDD). RCA methods provide tools to speed up the work of the process engineer troubleshooting an abnormal situation, and the review should help in selecting appropriate methods. It is intended as a tool to increase the awareness and the understanding of data-driven RCA methods and to promote their use. The focus on transient disturbances answers a need for methods to automate or facilitate RCA of transient disturbances in industrial processes or industrial machinery that was observed by the authors during discussions with service engineers.